New late Middle to early Late Ordovician U-Pb zircon ages of extension-related felsic volcanic rocks in the Eastern Pyrenees (NE Iberia): Tectonic implications - Martí, Joan (2019)
Pre-Variscan basement rocks from the Pyrenees provide evidence of several magmatic episodes with complex geodynamic histories from late Neoproterozoic to Palaeozoic times. One of the most significant episodes, consisting of several granitic and granodioritic bodies and volcanic rocks, mostly pyroclastic in nature, dates from the Late Ordovician period. In the Eastern Pyrenees, this magmatism is well represented in the Ribes de Freser and Núria areas; here, the Núria orthogneiss and the Ribes granophyre, both dated at c. 457-460 Ma, seem to form a calc-alkaline plutonic suite emplaced at different crustal levels. The presence of numerous pyroclastic deposits and lavas interbedded with Upper Ordovician (Sandbian-lower Katian, formerly Caradoc) sediments, intruded by the Ribes granophyre, suggests that this magmatic episode also generated significant volcanism. Moreover, the area hosts an important volume of rhyolitic ignimbrites and andesitic lavas affected by Alpine deformation. These volcanic rocks were previously attributed to late Variscan volcanism, extensively represented in other areas of the Pyrenees. Here we present the first five laser-ablation U-Pb zircon dates for this ignimbritic succession and two new ages for the Ribes granophyre. The ages of the ignimbrites, overlapping within error, are all 460 Ma, suggesting a genetic relationship between the plutonic and volcanic rocks and indicating that the Sandbian-Katian magmatism is much more voluminous than reported in previous studies, and possibly includes mega-eruptions linked to the formation of collapse calderas.